Abusive supervision as a response to follower hostility: a moderated mediation model - Camps, Jeroen (Journal of business ethics, 2020)
How and when does followers’ upward hostile behavior contribute to the emergence of abusive supervision? Although from a normative or ethical point of view, supervisors should refrain from displaying abusive supervision, in line with a social exchange perspective, we argue that abusive followership causes supervisors to experience low levels of interpersonal justice, stimulating abusive supervision in response. Based on uncertainty management theory, we further expect that the extent to which supervisors reciprocate the experienced injustice with abusive supervisory behavior is moderated by supervisors’ self-doubt. A multi-source field study as well as a vignette study following an experimental-causal-chain approach supported our hypotheses. Specifically, our results revealed that the indirect effect of abusive followership on abusive supervision through supervisors’ interpersonal justice is most pronounced when supervisors experience high levels of self-doubt. The practical and theoretical implications of our findings are discussed.